PKM Sel Surya Untuk Usaha Kolam Pancing Dusun IV Undian Desa Tadukan Raga Kecamatan STM Hilir Kabupaten Deli Serdang - Hestukoro, Soni; Tarigan, Jenny Sari; Tumanggor, Esto; Akhiruddin, Akhiruddin (JUBDIMAS ( Jurnal Pengabdian Masyarakat), 2024)
Fishing ponds are one of the attractive fishing tourism objects and are increasingly being developed to meet the needs of the community. The growth of this fishing pond turns out to provide benefits for entrepreneurs. Kakek fishing pond, which is located in Dusun IV Undian, Tadukan Raga village, STM Hilir subdistrict, Deli Serdang, is one of the fishing ponds that is always visited by customers every day. This pond with a total area of 900 chains is planted with tilapia and tilapia fish seeds. The problem faced by partners is the large cost of managing the fishing pond, including electricity costs to turn on the pump, fan and lights at night. Apart from that, the problem of wiring to reach the farthest part of the hut on the edge of the pond is another obstacle faced by partners. The implementing team offered to provide cottage lighting for fishing ponds based on solar panels as a solution. By holding this activity all the electrical power for lighting the pool can be supplied by solar cell installations.